KINETIKA PERMEASI KLOTRIMAZOL DARI MATRIKS BASIS KRIM YANG MENGANDUNG VIRGIN COCONUT OIL (VCO) - Lucida, Henny; Husni, Patihul; Hosiana, Vinny (Jurnal Riset Kimia, 2008)
ABSTRACT A kinetic study on the release of clotrimazole from a VCO containing creambase has been undertaken. The in-vitro release of the drug was studied by using a modification diffusion cell apparatus. Four formulations of clotrimazole cream were prepared, each contained either VCO or paraffin liquidum in the cream base. The amount of clotrimazole release were determined by UV spectrophotometer. Results showed that release of clotrimazole from all formulations followed Higuchi kinetics, the release rate constant from F1 (containing VCO) was significantly different than that from F1’ (containing paraffin liquidum) (p < 0.05). The rate constant of clotrimazole from F2 (containing VCO); F2’ (containing paraffin liquidum ) and F1 were not significantly different. Virgin coconut oil (VCO) was a potential cream base matrix regarding the release profile of clotrimazole from the matrix. Keywords : clotrimazol, VCO, permeation kinetic